THE EFFECT OF TEACHING THE SUBJECT OF ALGEBRARY EXPRESSIONS USING WEB 2.0 TOOLS ON THE PERMANENT SUCCESS OF MATHEMATICS OF 6TH GRADE STUDENTS1 - Polat, Veli; Aydın, Şevket (International Online Journal of Education and Teaching, 2023)
The aim of this study is to look into the touch on of utilizing web 2.0 tools in teaching algebraic expressions during the sixth-grade mathematics course on the long-term retention of students' mathematical achievement. Quantitative search methods and a quasi-experimental search design were employed for this study. The aim population consisted of sixth-grade students in Gaziantep during the 2021-2022 faculty member year. The taste was selected from two public schools in the Nurdağı zone of Gaziantep, which were included in this population. In the implementation phase, the topic of "Algebraic Expressions" was taught victimization net 2.0 tools in the experimental group, while the control group followed the orthodox curriculum. The data for this study were collected through and through the administration of the "Algebraic Expressions Achievement Test." The collected data were analyzed using the SPSS 24 software. The findings of this study revealed that thither was no significant remainder in the faculty member achievement test scores between the inquiry and control groups. Based on these results, it has been concluded that the use of web 2.0 tools in commandment algebraic expressions in mathematics lessons does not have a significant bear on on students' retention of mathematical knowledge compared to traditional teaching methods.